In Good Company : Managing Intellectual Property Issues in Franchising. - Organization, World Intellectual Property (IP for Business., 2019)
Franchising is one of the fastest and most popular means of business expansion. At the core of franchising is the licensing of intellectual property rights. Packed with examples and tips, this practical guide for business people outlines different types of franchise and takes you through the franchising process, identifying the key issues to consider at each stage.